PEMBERIAN PUPUK NPK DAN KOMPOS JERAMI PADA PERTUMBUHAN DAN HASIL PADI (Oryza sativa L) METODE SRI (SYSTEM OF RICE INTENSIFICATION) - Gloria Kaparang; Jeane M. Paulus; Stanley A. F. Walingkas (COCOS, 2017)
ABSTRACTThe goal of this research is to find out the influence of NPK fertilizer and straw compost to the growth and yield of rice paddy trough SRI (System Of Rice Intensification) method, conducted in Tara-Tara Dua Sub-District, West Tomohon District, Tomohon City for 5 months, from August to December 2015.This research was using Random Group Plan, and the factor is straw compost which is combined by NPK manure treatment consisted of P0 = 100 % NPK + 0 % straw compost, P1 = 75% NPK + 25% straw compost, P2 = 50% NPK + 50% straw compost, P3 = 25% NPK + 75% straw compost, P4 = 0% NPK + 100% straw compost. The result showed that the application of NPK fertilizer and straw compost to the plant growth rate were generally increased at 21 to 49 days after planting, and rapidly increased at 49 to 77 days after planting, then highly decreased at 77 to 91 days after planting. The application of NPK fertilizer and straw compost gave a high impact to the growth and production of rice paddy (dry weight plant, dry harvest grain yield/garden bed, and dry milled grain yield/garden bed). The application of NPK fertilizer can be replaced by using 25% - 100% or 4,5 Kg – 18 kg dosage of straw compost to the Dry Milled Grain as well as to the Dry Harvest Grain . The application of the NPK fertilizer and straw compost to dry weight plant ranged between 31,03 gram – 31,75 gram, to dry harvest grain 6,33 kg – 7,66 kg, and to dry milled grain 5,03 kg – 6,50 kg.The application of NPK fertilizer and straw compost did not affect the growth rate of plants, dry weights of plants, dry harvest grain per garden bed, and dry milled grain per garden bed. It means that the application of 25%-100% straw compost can replace 100% NPK fertilizer.The farmers have been suggested to use 100% rice straw compost in strew cultivation through SRI method.Keywoards : trough Sri, Impact fertilizer and Straw Compost, Tara-tara